2014
DOI: 10.1002/mop.28245
|View full text |Cite
|
Sign up to set email alerts
|

Novel LTCC switchable bandpass filter using vertically short-ended sir

Abstract: A novel compact low‐temperature cofired ceramic (LTCC) centrally loaded short‐ended stepped‐impedance resonator (SIR) is constructed in three‐dimensional (3D) environment and investigated to design a switchable bandpass filter (BPF). The size of the proposed SIR can be miniaturized greatly, because it is vertically folded in LTCC. The switchable passband of the BPF can be achieved by mounting PIN diodes on the surface of LTCC substrate. The simulated and measured results of the demonstration compact BPF are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Since tempering is a diffusion-controlled process involving the re-arrangement of carbon atoms in the microstructure, both temperature and time are expected to influence the tempering response following the Hollomon-Jaffe relationship [6,8]. Large ranges in temperature (from 100 ℃ to 500 ℃) and tempering duration (from 20 s to 10 7 s) have been used to investigate the influence of heat treatments, and the results have shown that the tempering temperature plays a more dominant role [9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since tempering is a diffusion-controlled process involving the re-arrangement of carbon atoms in the microstructure, both temperature and time are expected to influence the tempering response following the Hollomon-Jaffe relationship [6,8]. Large ranges in temperature (from 100 ℃ to 500 ℃) and tempering duration (from 20 s to 10 7 s) have been used to investigate the influence of heat treatments, and the results have shown that the tempering temperature plays a more dominant role [9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Various experimental techniques or apparatus such as X-ray diffraction (XRD), scanning electron microscopy (SEM) or transmission electron microscopy (TEM) have been used to understand the relation between the carbide movement in martensite and heat-treatment temperatures [25]. To date, most of the tempering studies report on the overall performance of the tempered materials and only a few address how individual phase (ferrite and martensite) properties are affected by tempering [9,26]. Even though the reduction of strength disparity between two phases was believed to lead to better formability of DP steels, none of the previous studies cited have attempted at quantifying the effects of tempering on the changes of individual phase properties of a DP980.…”
Section: Introductionmentioning
confidence: 99%